PERBEDAAN KEMAMPUAN MENULIS TEKS TANGGAPAN KRITIS SIWA KELAS IX SMPN 3 BENGKULU UTARA DENGAN SISWA KELAS IX SMPN 10 BENGKULU UTARA - Oktarina Widarsih; Syukri Hamzah; Didi Yulistio (Jurnal Korpus, 2018)
The purpose of this research is 1) to know the ability to write text of critical responses of students of class IX SMPN 10 Bengkulu Utara, 2) to know the ability to write text of critical responses of students of class IX SMPN 3 Bengkulu Utara and 3) to know the difference of writing ability of critical responses between students Class IX SMPN 3 North Bengkulu and students of class IX SMPN 10 North Bengkulu. This research uses quantitative descriptive method. The population of this research is the students of IX class SMPN 3 Bengkulu Utara and the students class IX SMPN 10 Bengkulu Utara, the sample is taken as many as 100 students. Data collection techniques use critical capability writing text tests. The data analysis technique used is unpaired T-test. The results showed that the ability to write text critical responses in students of class IX SMPN 3 Bengkulu North categorized enough and students class IX SMPN 10 North Bengkulu good category. There was no significant difference between students of IX class 3 of SMP 3 Bengkulu Utara with students of class IX SMP 10 Bengkulu Utara. From the results of this study as for suggestions submitted for both schools are more understanding of the structure of text, language rules, and spelling of Indonesian so that the writings of students more qualified. Keywords: Differences, Writing Capabilities, Critical Response Texts